Assistance for Prisoners to Obtain Free Legal Aid at the Gianyar Detention Center - Ni Made Sukaryati Karma; I Ketut Sukadana; I Made Aditya Mantara Putra; Kade Richa Mulyawati; Kadek Nadya Pramita Sari (Fakultas Hukum, Universitas Warmadewa, 2025)
Legal aid for the Indonesian people must be provided equally in accordance with the mandate of the 1945 Constitution of the Republic of Indonesia and the principles of equality before the law and the right to be represented by a lawyer, which are fundamental human rights. This right must be provided fairly, including to those who are less fortunate. For the less fortunate, this right is the responsibility of the state, which provides legal aid free of charge (Prodeo). The issue in society is the lack of awareness about their right to receive free legal aid (Prodeo) from the government. Additionally, the public is also unaware that legal organizations also have the duty to provide legal aid to the community. The legal education program conducted by the Warmadewa University Community Service Team aims to increase legal awareness regarding free legal aid and the procedures for obtaining this right, using methods such as lectures and question-and-answer discussions. This program is expected to enhance public knowledge so that individuals facing legal issues can be assisted by lawyers in resolving the legal problems they encounter.